Attitudes to antipsychotic drugs, and the quality of life of patients with schizophrenia - Kopyciński, Zbigniew; Czernikiewicz, Andrzej (Current Problems of Psychiatry, 2012)
There is no universal definition of the quality of life. Award proposed an interesting and clinically useful concept that the quality of life is the subject´s perception of interaction between severity of psychotic symptoms, side effects, including subjective responses to antipsychotic drugs and the level of psychosocial performance. Postneuroleptic dysphoria/negative attitudes towards drugs is one of the agents which have an influence on adherence and ultimately on outcome of the therapy. The aim of this study was analysis of relationships between subjective quality of life and negative attitudes towards drugs. Results show that negative attitudes towards drugs are correlated with lower quality of life.